Utilization Of The Shitsumon Education Application To Support Distance Learning at SDN Semplak 1 Bogor City - Deddy Sofyan, Tustiyana Windiyani (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This study aims to benefit the Shitsumon Education application in supporting distance learning. This research uses descriptive qualitative method. The research was conducted in Class 3 SDN Semplak 1 Bogor City with a total of 28 students. Based on the results of the questionnaire, it can be seen that the Shitsumon Education Application can support students in learning because when taking the evaluation test there is no need to write on paper but directly in the application. From these results it can be seen that 1% strongly disagree, 2% disagree, most of the 41% agree and 20% strongly agree that this application is useful for them and motivates them. This shows the use of this learning media is very effective and effective. to maximize learning outcomes. Thus this Shitsumon Education application is an alternative application in learning activities.